Responses of Brazilian business climate change: an analysis of the light of legitimate theory - Gibaut, Emerson Andrade; Dias Filho, José Maria (Revista de Administração da UFSM, 2016)
According to the Legitimate Theory, the organizations establish practices of social appreciation to ensure its continuity, which hence the hypothesis that, the bigger the company or more sensitive for the sector in relation to environmental issues, the greater will be the disclosure of practices. In addition, the present study aimed to verify how the size or sector of a company could affect the disclosure of their practices to cope with climate change. For this reason, we carried out a study with a sample composed of 22 companies present in the portfolio of Corporate Sustainability Index (CSI), in the year 2014, and listed on BM&FBOVESPA, who responded to a questionnaire on climate change. Based on the assumptions of the Legitimate Theory, in order to test the hypotheses formulated, we used the Kruskal Wallis test. The results indicated that there is no significant relationship between size and disclosure, but not between industry and disclosure program, which allows us to conclude that the size of the organization interfere positively in their level of environmental disclosure.